An investigation into the implementation of participative management in a rural school in the Pietermaritzburg district - Ngubane, Weekend Sehlulamanye (Rhodes University, Faculty of Education, Department of Education, 2006)
The primary purpose of this research was to investigate the extent to which rural schools understand and perceive the concept of participative management. The concept of participative management has been viewed as an ideal style of leadership and management for school development purposes. In South Africa's case, it is an educational policy which is expected to reign in all school management bodies. Many theorists envisaged participative management as enhancing active involvement of relevant stakeholders and it has been advocated by many scholars who believe it is the best leadership style in implementing democratic values to education, particularly South African rural education, which is still in a transitional stage. As an interpretive orientated study, this research had an interest in understanding the research participants' subjective experiences as well as their general perception of participative management. As case-study-driven research, it sought to investigate their understanding of the concept in their natural setting. This included various meanings they aligned with and attached to participative management, their attitudes, their interpretations and feelings towards it. The study employed a focus group data gathering technique in collecting data. The findings of this study suggest that participative management has been embraced by rural school management to a certain extent. There are potentially positive aspects that have been brought by participative management to the school, namely, shared vision, common goals, shared decision-making and general involvement of relevant stakeholders. However, the study has depicted a lack of ethical values on the side of some stakeholders and this hinders the smooth implementation of participative management. The study has also revealed that there are challenges facing rural schools in terms of parental involvement in school governance. Challenges such as lack of commitment to the school, illiteracy among adults and communication breakdown between the school and its parents are still rife in rural schools. Besides these challenges, the blood of participative management is flowing steadily in the veins of the rural school communities.
Keywords: Rural schools -- South Africa -- KwaZulu Natal -- Case studies; Rural schools -- Thailand -- Case studies; Education, Rural -- South Africa -- KwaZulu Natal -- Case studies; Black people -- Education -- South Africa; School management and organization -- South Africa; School principals -- South Africa; Educational leadership -- South Africa; Educational change -- South Africa; Management -- Employee participation -- South Africa